The Process of Playful Learning in Higher Education: A Phenomenological Study - Lisa Forbes (University of Windsor, 2021)
Higher education faculty strive to adopt pedagogical approaches that generate student engagement, motivation, and quality learning experiences. The literature on play has much to offer higher education. However, playful pedagogy remains an uncommon approach in education and is often represented in the literature as a practice utilized for a singular purpose and not as an underlying teaching philosophy. This phenomenological study examines the meaning of students' experiences of play as a foundation to learning. The themes that emerge are: 1) play is underutilized and devalued in higher education, 2) play cultivates relational safety and a warm classroom environment, 3) play removes barriers to learning, 4) play awakens students' positive affect and motivation, and 5) play ignites an open and engaged learning stance to enhance learning.